A(rt)ssenede '86. (Assenede, : Gemeentebestuur, 1986)
Ampe, Dominique ; Armborst Anette ; Armborst, Hans, Bachhuber, Liz. ; Beyls, Peter ; Bruyninckx ; Rob ; Balder ; Bauwens, Bart ; Bourgeois, Paul ; Brandts, Eric ; Carlier, Jan ; Cavens, Fri ; Cornelis, Beniti ; Crab, Jan ; Dusepulchre, Francis ; Dupont, Veerle ; De Roover, Marc ; De Rudder, Pim ; De Viser, Bea ; Dierickx, Karel ; Dey, Han ; Ellert, Petra ; Foulon, Hubert ; Franken, Michele ; Hioco ; Hesse, Herman ; Hemelrijckx, Jan ; Horvath, Pal ; Ernst, Joachim ; Jagenau, Ton ; Jacobs, Roel ; Juchtmans, Jus ; Kakedo, Yoshiyuki ; Kliege, Wolfgang ; Koenraad ; Lietaert, Dominique ; Lenoir, Lut ; Muller, Manfred ; Maes, Herman ; Maes, Agnes ; Mahieu, Frank ; Berrevoets, Fred ; Nora ; Par, Ady ; Pauwels, Tone ; Quivron, John ; Rijsinga, Henk ; Royen, Peter ; Reichler, Rita ; Raveel, Roger ; etc.
A(rt)ssenede '86, Assenede, 29, 30, 31 augustus 1986
boek